2023
DOI: 10.1038/s41375-023-02048-y
|View full text |Cite
|
Sign up to set email alerts
|

European LeukemiaNet laboratory recommendations for the diagnosis and management of chronic myeloid leukemia

Nicholas C. P. Cross,
Thomas Ernst,
Susan Branford
et al.

Abstract: From the laboratory perspective, effective management of patients with chronic myeloid leukemia (CML) requires accurate diagnosis, assessment of prognostic markers, sequential assessment of levels of residual disease and investigation of possible reasons for resistance, relapse or progression. Our scientific and clinical knowledge underpinning these requirements continues to evolve, as do laboratory methods and technologies. The European LeukemiaNet convened an expert panel to critically consider the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…+ der (22)t(9; 22) and 9/9p are negatively predictive in adults with Philadelphia chromosome-positive ALL [31]. These finding was further explored in another study published in the American Journal of Haematology, which not only confirmed these negative manifestations but also discussed the challenge of the tyrosine kinase inhibitor-resistant population and emphasized the need for a more in-depth understanding of BCR-ABL kinases [32]. Furthermore a study shows the importance of identifying tyrosine kinase inhibitor protection mechanisms through genetic for the better treatment of CML [33].…”
Section: Discussionmentioning
confidence: 86%
“…+ der (22)t(9; 22) and 9/9p are negatively predictive in adults with Philadelphia chromosome-positive ALL [31]. These finding was further explored in another study published in the American Journal of Haematology, which not only confirmed these negative manifestations but also discussed the challenge of the tyrosine kinase inhibitor-resistant population and emphasized the need for a more in-depth understanding of BCR-ABL kinases [32]. Furthermore a study shows the importance of identifying tyrosine kinase inhibitor protection mechanisms through genetic for the better treatment of CML [33].…”
Section: Discussionmentioning
confidence: 86%
“…Overall, 17% of CML patients (n = 21) progressed to either AP-CML (n = 11) or BC-CML (n = 10). A study conducted and all approved TKIs in technologically advanced countries (2,3,13). Furthermore, there was a significant difference between chronic- and advanced-phase patients concerning male-to-female ratio, hemoglobin level, WBC count, and platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic myeloid leukemia (CML) is a clonal myeloproliferative neoplasm of the hematopoietic stem cells (HSCs), marked by the uncontrolled excessive production of dysfunctional granulocytes and progenitors’ cells, in the bone marrow and peripheral blood (1). CML is the first aberrant chromosome abnormality described in a malignancy, known as the Philadelphia (Ph+) chromosome (2). The presence of Philadelphia chromosome t(9:22), which is a chromosomal reciprocal translocation between Abelson murine leukaemia (ABL) on the long arm of chromosome 9 and breakpoint cluster region (BCR) on chromosome 22, is a defining feature of CML (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary defining feature of CML for diagnosis is the presence of the BCR::ABL1 chimeric fusion oncogene, or Philadelphia chromosome (Ph), which arises from a t(9;22)(q34;q11) translocation between chromosomes 9 and 22 [ 2 ]. Based on the European LeukemiaNet (ELN) and MD Anderson (MDACC) criteria, CML progresses through three stages: chronic (CP), accelerated phase (AP), and blast crisis (BC), with each phase defined by increasing blast percentages, accumulation of additional cytogenic abnormalities, and other hematologic parameters [ 3 , 4 ]. However, since 2022, the World Health Organization (WHO) has removed the CML-AP designation and instead stratifies CML into CML-CP and CML-BP only, based on the presence of high-risk features [ 5 ].…”
Section: Introductionmentioning
confidence: 99%